From Planning to Scenario-Shaping of the Future - Alexander Khlunov (Foresight and STI Governance, 2009)
In an interview with the magazine, Deputy Minister of Education and Science of the Russian Federation Alexander Vitalyevich Khlunov spoke about the prerequisites, main tasks and some results of the forecast of scientific and technological development of the Russian Federation for the long term. He also shared his opinion on what effects the forecast can have on scientific and technological progress in Russia and how ready the country's professional communities are for such projects.